The Gujarat carnage - Engineer, Asghar Ali, 1939-2013. (New Delhi : Orient Longman, 2003)
Compilation of articles, interviews, and investigative reports.
Keywords: Genocide -- India -- Gujarat; Muslims -- India -- Gujarat; Hindus -- India -- Gujarat; Gujarat (India) -- Ethnic relations